2002
DOI: 10.2176/nmc.42.81
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic Treatment of Idiopathic Occlusion of the Foramen of Monro in Adults. Two Case Reports.

Abstract: Two adults presented with hydrocephalus due to idiopathic obstruction of the bilateral foramina of Monro, manifesting as clinical signs of chronically elevated intracranial pressure. No inflammation was present. The primary surgical treatment was neuroendoscopic reconstruction of the right foramen of Monro. A 37-year-old man had a spontaneous perforation of the septum pellucidum. The patient required a ventriculoperitoneal shunt, although postoperative ventriculography proved free passage of cerebrospinal flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…[1][2][3][4][5] After studying the other 8 cases of this entity, which have been published, we observed that the most frequent presenting symptom was headache, like in our case. It is more common in infants or children.…”
Section: Discussionsupporting
confidence: 57%
“…[1][2][3][4][5] After studying the other 8 cases of this entity, which have been published, we observed that the most frequent presenting symptom was headache, like in our case. It is more common in infants or children.…”
Section: Discussionsupporting
confidence: 57%
“…However, 10 of 13 patients combined from recent series had acceptable outcome without the need for a shunt after the procedure (Table 1). 8,11,13,15,16,21,25 Foraminoplasty may be performed safely in the presence of a thin avascular membrane covering the foramen. 13 However, if the foramen is atretic or obscured, there is increased risk of injury to the fornix.…”
Section: Discussionmentioning
confidence: 99%
“…Obstruction of the Monro foramen and consecutive hydrocephalus may be the result of thalamic and intraventricular neoplasia, colloid cysts, tuberculous masses, ventriculitis, vascular malformations and non-specific inflammatory conditions (1,4,6,7,14). Idiopathic occlusion of the foramen of Monro, a condition in which no background pathology could be found, is an extremely rare phenomenon, in which the foramen of Monro may be occluded by a membrane or may be atretic (5,16).…”
Section: Discussionmentioning
confidence: 99%
“…AV malformation of the choroid plexus (4,14), and basilar artery aneurysm or ectasia (7)), or iatrogenic complications. Idiopathic occlusion of foramen of Monro, a situation in which no clue can be detected to the etiology of foraminal obstruction, is an extremely rare phenomenon in adults with only five cases of bilateral and ten cases of unilateral obstruction reported in the literature (6,(10)(11)(12)(13)15). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation